Determinants of Return on Equity in Sharia Bank in Indonesia - Daulay, Muhammad Apis; Satriana, Desmi; Ardiansyah, Misnen (Al-bank: Journal of Islamic Banking and Finance, 2025)
This study examines the influence of several financial indicators Firm Size, BOPO, NOM, DER, FDR, DPK, NPF, and CAR on Return on Equity (ROE) in Indonesian Sharia Banks from 2013 to 2022. Using a quantitative approach with secondary data sourced from the Financial Services Authority (FSA) and banks’ annual reports, the study employed panel data regression with model selection among Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). The REM was identified as the most suitable model. The results reveal that NOM and DPK have a positive and significant impact on ROE, while BOPO, DER, and NPF negatively and significantly affect ROE. These findings offer insights into optimizing financial strategies in Islamic banking in Indonesia